Explaining growth : - McMahon, Gary (Palgrave MacMillan, 2003)
Explaining Growthattempts to compile the most comprehensive assessment of growth in developing and transition countries. The first phase has sought to review and discover broad similarities and comparable experiences in six regions spanning the developing world. In each region, studies were undertaken on sources of growth, markets and growth, microeconomic determinants of growth, and the political economy of growth. These reviews provide the framework for the in-depth country case studies in Phase II. This volume summarizes the main results of the regional analyses and sets the stage for the country studies.